STUDI ALUR PERENCANAAN MUSEUM TERTUTUP TROWULAN MOJOKERTO - Citra Maharani; Saghani Ahmad Sadewa; Han Ay Lie; Parang Sabdono (Jurnal Karya Teknik Sipil, 2015)
Trowulan Covered Museum is a museum to be built in Mojokerto and its function is not only to implement the protection of objects of cultural heritage relics of the Majapahit Empire, but throughout the ancient relics in East Java. Therefore, the longer the collection becomes more and more. To overcome this it will be built Trowulan Covered Museum with wider designed located about 2 kilometers from the old museum is on the road Mojokerto-Jombang km. 13. The Trowulan Covered Museum consists of 3 floors and one basement where each floor is divided into four segments, each segment is connected by a ramp. Trowulan Covered Museum structure is designed based on Design Capacity method or SRPMK (Struktur Rangka Penahan Momen Khusus). SRPMK main concept is to make the column stronger than the beam (strong column, weak beam) that is expected to occur in the plastic joint which can emit a beam of energy in the quake. The main guideline in planning drawn from imposition Regulations, 1987, Concrete SNI 03-2847-2013 and SNI 03-1726-2012 earthquake and earthquake response parameter values obtained from the website Puskim Ministry of Public Works for the city of Mojokerto and assisted SAP 2000 version 14. Item jobs are taken into account include the overall structure of the work, namely stairs, ramps, floor plate, beams, columns, beam-column connections, and foundation.